Lost in the jungle stage 7 - Hunt, Rodrick (United Kingdom Oxford University Press, 2012)
the children are whisked into a jungle environment where they encounter explorers, possibly get trapped in nets, and traverse waterfalls. They ultimately discover a lost city and bring back a plant as a gift for their mother, making the adventure both magical and personal.
These books are part of the Oxford Reading Tree Level 7: Stories series, designed for children who are developing confidence and fluency in reading. The stories continue the popular adventures of Biff, Chip, Kipper, Wilf, and friends, combining everyday school life with imaginative journeys sparked by the magic key.